Implementation of the example/non-example learning model to improve learning outcomes in the basics of building design, modeling and information subject - Kinanti Wijaya; Elza Melany Simatupang (Universitas Negeri Padang, 2025)
This study aimed to examine the effectiveness of the Example/Non-Example cooperative learning model in improving student learning outcomes in the subject Fundamentals of Design, Modelling, and Building Information (DPIB) for Grade X students at SMK Negeri 1 Percut Sei Tuan during the 2024/2025 academic year. The research was driven by low student achievement, with over 50% failing to meet the school’s minimum passing grade of 70, highlighting the need for more engaging and student-cantered learning strategies. The Example/Non-Example model was chosen for its potential to foster critical thinking through visual analysis and collaborative learning. This research employed Classroom Action Research (CAR), consisting of two cycles with the stages of planning, action, observation, and reflection. The participants were 31 Grade X DPIB students. Data was collected using validated multiple-choice tests with 22 items in Cycle I and 23 items in Cycle II. The findings revealed an increase in the average score from 75.51 in Cycle I to 80.96 in Cycle II, representing a 26.08% improvement. These results indicate that the Example/Non-Example model is effective in enhancing student achievement and can serve as an alternative instructional strategy for improving competency attainment in vocational subjects.